2010
DOI: 10.1111/j.1532-950x.2010.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro Total Hip Replacement for Dogs and Cats: Surgical Technique and Outcomes

Abstract: Micro THR is a viable option to treat disabling disorders of the hip. More than 170 cat and small dog breeds, and many mixed breeds, could benefit from Micro THR surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 26 publications
10
75
0
11
Order By: Relevance
“…17 The success of THR systems designed for small and toy breed dogs and cats has been previously reported for a different THR system. [18][19][20] Zurich has recently made available a mini Zurich THR system for use in small breed dogs weighing 10-kg to 16-kg body weight. Zurich has plans for the release of THR implants intended for patients smaller than 10-kg body weight in the near future.…”
Section: Current Controversies/future Considerationsmentioning
confidence: 99%
“…17 The success of THR systems designed for small and toy breed dogs and cats has been previously reported for a different THR system. [18][19][20] Zurich has recently made available a mini Zurich THR system for use in small breed dogs weighing 10-kg to 16-kg body weight. Zurich has plans for the release of THR implants intended for patients smaller than 10-kg body weight in the near future.…”
Section: Current Controversies/future Considerationsmentioning
confidence: 99%
“…Micro-THRs have been reported in a limited number of cats for the treatment of femoral capital physeal fractures, coxofemoral luxation and as revision surgeries after unsuccessful FHNEs. 4,[9][10][11][12]22 Good-to-excellent clinical outcomes were reported in most of the cats in these studies. Despite this, recurrent lameness has been reported in cats after micro-THR.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatic neurapraxia is reported as a rare complication after total hip arthroplasty. In the studies citing sciatic neurapraxia as a postoperative complication after total hip arthroplasty, the incidence rate ranged from 0.7% to 3.1% (15,22,24,27,32,34). The largest of those studies, on 1000 consecutive total hip arthroplasties with 967 primary arthroplasties, indicated a 1.8% incidence rate of sciatic neurapraxia, closely matching the incidence rate in our study (2%).…”
Section: Discussionmentioning
confidence: 99%